(untitled) (Research, Society and Development, 2025)
Rice (Oryza sativa L.) is a major staple food, cultivated worldwide. In Brazil, irrigated rice represents the dominant production system, especially in the southern region. Among the cultivars, IRGA 424 RI stands out for its high yield and agronomic stability. Seed treatment is a key practice for pathogen control, but it may influence physiological quality. This study aimed to evaluate the effects of different seed treatments—with and without the addition of a protector—on the physiological quality of IRGA 424 RI rice seeds. The experiment was conducted at the Federal University of Pelotas (UFPel), using industrial seed treatment with recommended doses of fungicide (Maxim Advanced®), insecticide (Cruiser Opti®), and protector (Permit Star®). Germination, cold test, and emergence in trays were assessed over 0, 15, 30, 45, 60, and 90 days of storage. Seeds treated with fungicide + insecticide showed superior physiological performance compared to untreated seeds and those treated with the protector alone. The addition of dietholate (protector) negatively affected seed quality when applied alone but had no negative effects when combined with fungicide and insecticide. The results indicate that seed treatment did not reduce physiological quality during the storage period.